Genome-wide epigenetic landscape of pig lincRNAs and their evolution during porcine domestication. (29th October 2018) - Li, Cencen; Zou, Cheng; Cui, Yong; Fu, Yuhua; Fang, Chengchi; Li, Yao; Li, Jingxuan; Wang, Wen; Xiang, Hui; Li, Changchun
Aim: We aimed to identify previously unreported long intergenic noncoding RNAs (lincRNAs) in the porcine liver, an important metabolic tissue, and further illustrate the epigenomic landscapes and the evolution of lincRNAs.Materials & methods: We used porcine omics data and comprehensively analyzed and identified lincRNAs and their methylation, expression and evolutionary patterns during pig domestication.Results: LincRNAs exhibit highly methylated promoter and downstream regions, as well as lower expression levels and higher tissue specificity than protein-coding genes. We identified a batch of lincRNAs with selection signals that are associated with pig domestication, which are more highly expressed in the liver than in other tissues (19:10/8/6/3/2/1/1). Interestingly, the lincRNA linc-sscg1779 and its target gene C6, which is crucial in liver metabolism, are differentially expressed during pig domestication.Conclusion: Although they may originate from noisy transcripts, lincRNAs may be subjected to artificial selection. This phenomenon implies the functional importance of lincRNAs in pig domestication.